Controllable thermal-frequency tuning of a THz gyrotron - Li Luo; Chao-Hai Du*; Xiang-Bo Qi; Zheng-Di Li; Shi Pan; Ming-Guang Huang; Pu-Kun Liu* (IEEE Trans. Electron Devices, 2018)
Gyrotron performance is sensitive to cavity structure parameters, and the cavity shape is temperature dependent due to thermal deformation induced by temperature rise from ohmic loss power on finite-conductivity cavity wall. Accordingly, this paper studies a frequency-tuning scheme for terahertz gyrotron by properly controlling the cavity thermal deformation. By combining gyrotron nonlinear theory and finite-element method software, controllable thermal-frequency-tuning capability of a continuous-wave 263-GHz gyrotron is systematically investigated, toward maintaining gyrotron operating under gyromonotron condition in frequency-tuning band, and achieving high efficiency in broadband frequency-tuning range. After studying cavity thermal distribution, structure deformation, and electron beam-wave interaction, an optimized cavity structure with transition sections on both ends is proposed. Simulation predicts that with the two-transition-section cavity, via additional thermal tuning, the continuous-frequency-tuning band is capable of reaching 1.75 GHz, which is 5 times of the initial bandwidth. Furthermore, using the thermal-frequency-tuning technology, impressive high efficiency above 17% is obtainable in the whole frequency-tuning range.